Case Report: Paraganglioma in the sellar region: longitudinal observation and surgical outcome - Wang, Yingjie; Yang, Xuan; Ma, Qianquan; Nicholas, Van Halm-Lutterodt; Sun, Jianjun; Zhao, Xiaofang; Liu, Weihai; Yang, Chenlong (Frontiers in Oncology, 2023)
Background: Paraganglioma in the sellar region is an extremely rare entity, with a limited number of cases reported in the literature. Due to the paucity of clinical evidence, the diagnosis and treatment of paragangliomas in the sellar region remain challenging. Herein, we reported a case of sellar paraganglioma with parasellar and suprasellar extension. Particularly, the dynamic evolution of this benign tumor within a 7-year longitudinal observation was presented. Additionally, the relevant literature regarding sellar paraganglioma was comprehensively reviewed. Case description: A 70-year-old woman presented with progressive visual deterioration and headache. Brain magnetic resonance imaging demonstrated a mass in the sellar region with parasellar and suprasellar extension. The patient refused surgical treatment. Seven years later, brain magnetic resonance imaging showed the lesion significantly progressed. Neurological examination revealed bilateral tubular contraction of visual fields. Laboratory examinations showed endocrine hormone levels were normal. Surgical decompression was performed via a subfrontal approach, and subtotal resection was achieved. Histopathological examination confirmed a diagnosis of paraganglioma. Postoperatively, she developed hydrocephalus, and ventriculoperitoneal shunting was performed. Eight months later, cranial CT showed no recurrence of the residual tumor, and the hydrocephalus had been relieved. Conclusion: Paraganglioma occurring in the sellar region is rare, and the preoperative differential diagnosis is difficult. Owing to the infiltration to the cavernous sinus and internal carotid, complete surgical resection is usually impracticable. There has been no consensus regarding postoperative adjuvant radiochemotherapy for the tumor residue. In-situ recurrence and metastasis have been reported in the literature, and close follow-up is warranted.